Extracts from strawberry by-products rich in phenolic compounds reduce the activity of apple polyphenol oxidase - Villamil Galindo, Johan Esteban (2020)
The ultrasound-assisted extraction of phenolic compounds from strawberry by-products was studied varying the solvent type (water, ethanol 80%, methanol 80%, and acetone 80%), the formic acid concentration (0 and 0.5%), and the number of extraction steps (1 and 2). Total phenolic and total flavonoid compounds were determined spectrophotometrically and analyzed by PAD-HPLC. The antioxidant capacity (DPPH and FRAP assays) and the ability of extracts to inhibit apple (Malus domestica cv. ‘Red Delicious’) polyphenol oxidase (PPO) were also investigated. Extracts with acidified methanol in two-steps yielded the highest phenolic compound concentration (15.01 g/kg), and the highest antioxidant capacity. Agrimoniin was the major polyphenol found, and the extraction with acetone in two-steps produced the highest yield (2.45 g/kg). This ellagitannin was the only polyphenol that correlated (R2 > 0.80, p < 0.05) with the antioxidant capacity. Water and ethanol showed the lowest phenolic compound yields. However, extraction with these green solvents (water or ethanol) in two-steps showed polyphenol contents similar to those obtained with methanol or acetone in one-step (≈9 g/kg). Additionally, extracted polyphenols (0.24 g/L) produced 30% apple PPO inhibition, in a reversible ‘uncompetitive’ inhibition. Results showed the high revalorization potential of strawberry by-products as a low-cost source of polyphenols, with antioxidant and anti-browning effects.